RESPON IKAN NILA (OREOCHROMIS NILOTICUS) DAN IKAN LELE (CLARIAS GARIEPINUS) YANG DIINFEKSI AEROMONAS HYDROPHILLA DENGAN EMPAT TINGKAT PASASE - ANGGI, ANGGI; PASARIBU, TANIA A; HUTABARAT, NAOMI; DAMAYANTI, SILVI M; KRISTIN, ESTER P; FAKHRI, MUHAMMAD; ANJANI, TIARA P; KURNIAWAN, ARDIANSYAH (GANEC SWARA, 2023)
Tilapia and catfish are some of the freshwater fisheries commodities that occupy the top rank in terms of the amount of production produced. Disease attacks in Tilapia and Catfish cultivation such as Motile Aeromonas Septicemia (MAS) can be detrimental to fish farmers. Motile Aeromonas Septicemia (MAS) disease is caused by the bacteria Aeromonas hydrophilla. This research aims to determine the differences in the physical condition of Tilapia and Catfish which were injected with Aeromonas hydrophilla bacteria and had been treated using the Koch Postulate method four times to reach 50% fish mortality. In this study, the Tilapia and Catfish samples used were 6-8 cm in size with a bacterial infection dose of 0.1ml/fish. Tilapia showed clinical symptoms of thin fins and the injection site began to become inflamed, while catfish experienced bleeding and wounds. Catfish tend to experience more serious injuries after exposure to A. hydrophilla compared to Tilapia due to differences in response to disease symptoms. Tilapia fish show symptoms of loose scales due to bacterial infections such as Aeromonas dhakensis, Pseudomonas mosselii, and Microbacterium paraoxydans.